The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1080/00071669889033
|View full text |Cite
|
Sign up to set email alerts
|

Ascaridia galli infections in free-range layers fed on diets with different protein contents

Abstract: 1. One hundred and twenty 17-week-old Lohman Brown hens were divided into 4 groups. Groups 1 and 3 were given a diet with 180 g protein/kg and groups 2 and 4 were given a diet with 140 g protein/kg. Groups 1 and 2 were orally infected with 500 (+/- 50) embryonated Ascaridia galli eggs. 2. Marked differences in mean weekly weight gain for the 4 groups were observed. 3. Hens given 140 g protein/kg had a significant lower mean worm burden of adult A. galli worms and a significant lower weight gain compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
(32 reference statements)
4
15
0
Order By: Relevance
“…This indicates that the acute P. multocida infection had a negative effect on the egg production which is in accordance with previous observations (Campi et al, 1990). Infections with A. galli may decrease egg production in layers (Permin et al, 1998a); however, the missing effect observed in this study might be related to the relatively high age of chickens when infected (Kerr, 1955).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that the acute P. multocida infection had a negative effect on the egg production which is in accordance with previous observations (Campi et al, 1990). Infections with A. galli may decrease egg production in layers (Permin et al, 1998a); however, the missing effect observed in this study might be related to the relatively high age of chickens when infected (Kerr, 1955).…”
Section: Discussionsupporting
confidence: 93%
“…Weight gain was depressed in the group infected with P. multocida as a single infection and in the two groups additionally infected with A. galli either as a primary or secondary infection. Acute P. multocida infections are known to cause anorexia and subsequent weight depression as it has also been described for A. galli (Rhoades, 1964;Ikeme, 1971;Nagi et al, 1990;Permin et al, 1998a). The two double infected groups never reached a weight as high as the other groups, and at the end of the experiment especially the weight gain of the group ®rst infected with A. galli and subsequently with P. multocida was lower compared to all the other groups.…”
Section: Discussionmentioning
confidence: 63%
“…It has been proposed that worm infection may increase during the winter months if the litter becomes wet (Methling et al, 1994). Other suggested factors that may potentially influence worm burdens include stocking rate (Permin et al, 1998a), and/or the diet (Permin et al, 1998b), but we did not observe any clear patters in this respect. Although our results underline the complex infection dynamics of ascarid infections in laying hen flocks, it was confirmed that the magnitude of A. galli infection was not solely linked to whether the chickens had outdoor access or not.…”
Section: Discussionmentioning
confidence: 83%
“…This may be due to an unattractive range area because there is no overhead cover and because feed is provided indoors (Bubier and Bradshaw, 1998). This involves a considerable risk of welfare problems (Bestman and Wagenaar, 2003), leaching of nutrients to the ground water and parasitic infections (Permin et al, 1998 and1999). Moreover, the feeding strategies in organic egg production systems are widely based on purchased feed, synonymous with a huge import of nutrients to the system.…”
Section: Introductionmentioning
confidence: 99%